Penggunaan Dandelion (Taraxacum officinale) dalam Pakan Terhadap Performa Kalkun (Meleagris gallopavo): Utilization of Dandelion (Taraxacum officinale) in the Diet on Turkey (Meleagris gallopavo) Performance (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2020)
The aim of this study was to evaluate fresh dandelion leaves on  turkey performance. The study used a complete randomized design of 4 treatments and 6 replications. A total number of 24 turkeys (Meleagris gallapavo)-12 week-old were used in this 5 weeks of feed trial. The experimental animals were fed with the diet containing  37% of commercial broiler starter diet, 40% rice bran and forage (water hyacinth and fresh dandelion leaves).  The treatments with fresh dandelion leaves addition were P0: 0%, P1: 5%, P2: 10%, and P3: 15%. The variables observed were bio active compound in dandelion leaves, daily behavior and turkey performance.  Data were analyzed by Analysis of Variance (ANOVA) and the significant differences between treatments were analyzed by Duncan's Multiple Range Test. The results showed that dandelion leaves contain flavonoids, tannins, saponins and steroids, vitamin D were 17.37 ppm and antioxidants IC50 have an antioxidant activity with a value of 102.31. Observation of daily behavior showed that turkeys behavior was dominated by eating and resting activities, where the highest frequency of resting activities was 0.43 per second (P0). Turkey performance were not significantly different on feed consumption, carcass weight, carcass percentage for all treatments but  significantly different  (p